Feasibility Study of Case-Based Instructional Materials for Enhancing Critical Thinking Skills in Doctoral Programs: A Development Research Approach - Wuryandani, Wuri; Fathurrohman, Fathurrohman; Nur Rohmah , Evy Nur Rohmah; Salsavira Cahaya Ningrum, Dita (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Teaching materials are a vital part of teaching, especially in higher education. Although teaching materials have been used in learning, the reality is that the availability of teaching materials that support the learning process using a case study approach in the Doctoral Program in Primary Education is still very limited, especially in the course Theory and Application of Civic Education in Primary Schools, which requires a case study approach as a stimulus for learning. This study also addresses the challenge of doctoral students' critical thinking skills through learning using the developed teaching materials. Method: This study uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, which specifically focuses on the development and validation of the feasibility of case study-based teaching materials. Results: The developed case study-based teaching materials showed very feasible results from various expert judgments. Validation by language experts resulted in an average score of 80%, while material experts gave a score of 90%, and media experts gave a feasibility score of 93%. Novelty: The case study-based teaching materials developed have a complete range of features tailored to field requirements, such as the availability of case study assignments for students that are integrated through barcode scanning to save time in the learning process. This accessibility makes it easier for both lecturers and students to access the assignments given and complete them on time despite the busy schedules of doctoral program lecturers and students.